Peningkatan Pengetahuan dan Keterampilan Kader Posbindu dalam Pengukuran Tinggi Badan Prediksi Lansia, Penyuluhan Gizi Seimbang dan Hipertensi Studi di Kecamatan Grogol Petamburan, Jakarta Barat - Fatmah Fatmah; Yusran Nasution (MEDIA MEDIKA INDONESIANA, 2012)
Increased Posbindu cadres knowledge and skills on elderly predicted height measurement, balanced nutrition and hypertension education among elderly in Grogol Petamburan Subdistrict, West JakartaBackground: One strategy to increase the coverage of the elders’ visit to elders integrated service post (Posbindu) by conducting a training on improving the skills of cadres. They have tasks to measure height, weight and provide nutritional counseling for elderly. Many elderly can not be measured in standing height due to paralysis, disability and stooped due to kyphosis and osteoporosis. The results of the nutritional status assessment of elderly should be followed up by balanced nutrition and hypertension education. Theaim of study was to test the effect of training on the knowledge and skills of Posbindu cadres in predicted height and balanced nutrition counseling of elderly.Method: Study design was quasi-experimental one group pretest posttest towards 41 respondents (36 Posbindu cadres and 5 staffs of community health center) at Grogol Petamburan Subdictrict who have been trained previously. Knowledge were measured with a pre-post test questionnaire and the skills of cadres were observed for 3 months post-training using the checklist form.Result: Mean score of knowledge had significant difference between before and after training (p=0.000) and its increased by 22 points. There was significant difference between cadres skills before and after training in predicted height and balanced nutrition education (p=0.000). The level of cadres’ skills on moderate and high had significant difference after training.Conclusion: Cadres training improves performance of Posbindu cadres.Keywords: Training, posbindu cadres, knowledge, antropometric skills, balanced nutrition educationABSTRAKLatar belakang: Salah satu strategi upaya peningkatan cakupan kunjungan lanjut usia (lansia) ke posyandu lansia (Posbindu) adalah membekali keterampilan kader melalui pelatihan. Tugas kader antara lain melakukan pengukuran tinggi badan dan berat badan serta memberikan penyuluhan gizi bagi lansia. Namun kegiatan pengukuran antropometri dan penyuluhan gizi belum dilakukan secara tepat di Posbindu. Tujuan penelitian adalah untuk meningkatkan pengetahuan dan keterampilan kader Posbindumelalui pelatihan keterampilan antropometri tinggi badan prediksi (TB) dan penyuluhan gizi seimbang serta hipertensi lansia.Metode: Disain penelitian menggunakan metode quasi eksperimental dengan rancangan one group pretest-posttest design pada 41 responden (36 kader Posbindu dan 5 petugas puskesmas) di Kecamatan Grogol Petamburan. Peningkatan pengetahuan diukur dengan angket pre-post test dan keterampilan kader diamati selama 3 bulan pasca pelatihan menggunakan form checklist.Hasil: Rerata skor pre dan post-test pengetahuan pengukuran antropometri lansia berbeda makna dan meningkat sebesar 22 butir. Perbedaan rerata keterampilan kader sebelum dan setelah pelatihan pada antropometri tinggi badan prediksi dan penyuluhan gizi seimbang lansia. Ada perbedaan keterampilan responden dengan tingkat cukup dan baik bila dibandingkan sebelum dan setelah pelatihan.Simpulan: Pelatihan kader meningkatkan pengetahuan dan kinerja kader Posbindu.